The Influence of the Media on the Perception of Endophobia - -Toukoumidis, Angel Torres; -Mendoza, Camila Villacís; Alieto, Ericson O.; -Chiguano, Moisés Pallo (Dirasat: Human and Social Sciences, 2025)
Objectives: The research aims to explain how media influences the perception of endophobia and contribute to construction of negative stereotypes. Methods: This study employs a mixed-methods approach, combining structured surveys conducted with 136 participants from diverse demographic groups in Ecuador to assess awareness and perceptions of endophobia, along with a qualitative content analysis of media outputs to examine framing and narratives. The data were analyzed using IBM SPSS v.29 for statistical analysis and thematic analysis to understand media influence on endophobia and the formation of stereotypes. Results: The study’s results indicate a limited awareness of the term "endophobia," particularly among younger and less educated individuals. Furthermore, the media’s role in exacerbating endophobia was highlighted, with significant differences in perception based on gender, age, and education level. analysis revealed that language used by media significantly affects public perception, particularly among younger individuals, and there is a general dissatisfaction with the quality of journalism regarding endophobia. The findings underscore the need for more responsible and ethical media practices, increased educational efforts to raise awareness about endophobia, and promotion of media literacy to help individuals critically assess media content. Conclusions: The study concludes that addressing the representation of endophobia in the media is crucial for fostering a more inclusive and cohesive society. Future research should expand the sample size and geographic scope, conduct longitudinal studies, and adopt interdisciplinary approaches to further understand and mitigate the impact of media on endophobia.